2018
DOI: 10.1186/s12885-018-4856-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the fibrinogen/albumin ratio (FAR) in patients with operable soft tissue sarcoma

Abstract: BackgroundCoagulation and nutrition play important roles in cancer progression. The aim of the present study is to evaluate the prognostic value of the preoperative fibrinogen/albumin ratio (FAR) in surgical patients with soft tissue sarcoma (STS) and to compare this value with other inflammatory biomarkers. In addition, we investigated the relationship between FAR and the clinicopathological characteristics of STS patients.MethodsWe included 310 STS patients in this retrospective study. Kaplan-Meier curves, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
8
29
1
Order By: Relevance
“…Furthermore, we established that preoperative elevated FARI is associated with other inflammatory markers, including high PLR and NLR and low PNI. Consistent with our findings, a study of soft tissue sarcoma confirmed that elevated FARI is remarkably associated with inflammatory markers such as NLR and PLR (29). Interestingly, in our study, we discovered that patients with high FARI more likely require open surgery, while patients with low FARI more likely require laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, we established that preoperative elevated FARI is associated with other inflammatory markers, including high PLR and NLR and low PNI. Consistent with our findings, a study of soft tissue sarcoma confirmed that elevated FARI is remarkably associated with inflammatory markers such as NLR and PLR (29). Interestingly, in our study, we discovered that patients with high FARI more likely require open surgery, while patients with low FARI more likely require laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study, to best of our knowledge exploring the relationship between the preoperative elevated FARI and a more malignant GIST. The results of previously published studies on the relationship between FARI and soft tissue sarcoma (29), hepatocellular cancer (30), and breast cancer (31), also support our conclusions. Furthermore, we established that preoperative elevated FARI is associated with other inflammatory markers, including high PLR and NLR and low PNI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…confirmed that patients with operable soft tissue sarcoma with a decreased FAR had a longer median survival time and a lower 5-year OS rate than those with high FAR, and the cut-off value of FAR in this study was 0.0726 [30]. To our best knowledge, the reported FAR cut-off value of 0.079 has been used for the first time to investigate its prognostic power in patients with PC.…”
supporting
confidence: 72%
“…Fibrinogen, a glycoprotein synthesized by the liver, is produced in response to inflammation or activation of the coagulation system and plays an important role in the coagulation cascade. 2 Inflammation is a hallmark of cancer, and malignant tumors compromise the coagulation, anticoagulation, and fibrinolysis systems of the body through various mechanisms, resulting in abnormal coagulation function and fibrinogen elevation. 3 Fibrinogen is an acute-phase-response protein that can increase under systemic inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%